Administrators need to be prepared to face VUCA world - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 26 October 2021 - The management of higher education organisations today should be rejuvenated so that the university can produce graduates who are skilled and relevant to the field of future employment.